Bisphenol A (BPA) as a Contributing Factor to Decreased Fertility in Humans: a Review of the Latest Evidence - Kania, Martyna; Adamowska, Agnieszka; Śniatała, Alicja; Bartkowiak, Hanna; Grubski, Damian; Ziarnik, Kacper; Nadolny, Filip; Jabłoński, Jędrzej (Journal of Education, Health and Sport, 2024)
Introduction Bisphenol A (BPA) is a synthetic compound widely used in producing consumer plastics like polycarbonate and epoxy resins. Recognized as an endocrine-disrupting chemical (EDC), BPA has been linked to various adverse health effects, including impacts on human fertility. Exposure to BPA has been associated with infertility risks not only through direct mechanisms but also by causing transgenerational effects, potentially compromising fertility in future generations. Aim of the Study This review aims to summarize recent evidence identifying BPA as an environmental contributor to infertility in humans. We explore mechanisms through which BPA disrupts the endocrine system, focusing on its effects on the hypothalamic-pituitary-gonadal (HPG) axis, oogenesis, spermatogenesis, and embryo implantation. Additionally, we discuss research on BPA’s potential long-term reproductive risks across generations and assess strategies for reducing BPA exposure. Materials and Methods We reviewed epidemiological, clinical, and experimental studies published over the past decade, with a search conducted in PubMed and Google Scholar. Both human and animal model studies were considered to provide a comprehensive perspective. Search terms included "Bisphenol A," "fertility," "endocrine disruptors," "spermatogenesis," "oogenesis," and "transgenerational effects." Conclusions BPA, an EDC ubiquitous in the environment, is shown to disrupt male and female fertility. Expanding research and regulatory measures are needed to reduce the reproductive health risks posed by BPA exposure to protect current and future generations.